Towards characterization of photo-excited electron transfer and catalysis in natural and artificial systems using XFELs. (14th September 2016) - Alonso-Mori, R.; Asa, K.; Bergmann, U.; Brewster, A. S.; Chatterjee, R.; Cooper, J. K.; Frei, H. M.; Fuller, F. D.; Goggins, E.; Gul, S.; Fukuzawa, H.; Iablonskyi, D.; et al.
Abstract : The ultra-bright femtosecond X-ray pulses provided by X-ray Free Electron Lasers (XFELs) open capabilities for studying the structure and dynamics of a wide variety of biological and inorganic systems beyond what is possible at synchrotron sources. Although the structure and chemistry at the catalytic sites have been studied intensively in both biological and inorganic systems, a full understanding of the atomic-scale chemistry requires new approaches beyond the steady state X-ray crystallography and X-ray spectroscopy at cryogenic temperatures. Following the dynamic changes in the geometric and electronic structure at ambient conditions, while overcoming X-ray damage to the redox active catalytic center, is key for deriving reaction mechanisms. Such studies become possible by using the intense and ultra-short femtosecond X-ray pulses from an XFEL, where sample is probed before it is damaged. We have developed methodology for simultaneously collecting X-ray diffraction data and X-ray emission spectra, using an energy dispersive spectrometer, at ambient conditions, and used this approach to study the room temperature structure and intermediate states of the photosynthetic water oxidizing metallo-protein, photosystem II. Moreover, we have also used this setup to simultaneously collect the X-ray emission spectra from multiple metals to follow the ultrafast dynamics of light-induced charge transfer between multiple metal sites. A Mn–Ti containing system was studied at an XFEL to demonstrate the efficacy and potential of this method.